Model Mekanisme Patahan Gempa Bumi Tarutung 2022 Mw 5.8 - Endah P. Sari; Resa Idha; Hendro Nugroho; Syahrul Humaidi; Andrean V. H Simanjuntak; Umar Muksin (LPPM STIKOM Tunas Bangsa, 2023)
On October 1, 2022, an earthquake with a magnitude of 5.8 shook the Tarutung area which was generated by an active fault at a shallow depth of 10 km. In this study, relocating the hypocenter and determining the mechanism of the earthquake was carried out to understand the active tectonic structure. The distribution of hypocenter relocation figures a pull-apart pattern at shallow depths. The earthquake mechanism shows a dextral pattern in the Southwest – Southeast direction with a strike of 138º – 158º. The aftershocks are more dominantly distributed in the pull-apart system in the southeastern part and show the greater part of the transfer of seismic static stress to the southeastern side of the Toru fault. The pull-apart tectonic system scheme in the Tarutung basin with secondary faults as extensional faults is proposed to be a fault source model that forms a negative-flower structure geological pattern. The results of this study can be used as a reference for studying the Tarutung tectonic system and applied as a mitigation study.